The Effect of Board Size, Capital Structure, Political Connection and Firm Size on Firm Performance - Galuh Pratiwi Bahar; Yudhi Herliansyah (Management Analysis Journal, 2023)
To study the factors that impact the company's performance in non-financial companies listed on the Indonesia Stock Exchange. This study analyzes a sample of 190 non-financial companies listed on the IDX from 2015 to 2019, total 950 samples. This data analysis method is carried out with the aid of the EViews (Econometric Views) version 11 software. The findings indicate that while the size of the company has a significant negative effect on performance, board size, financial structure, and political connections have no effect. This study contains limitations in terms of measuring company performance, one of which is the study's reliance on variables relating to political connections. This research is beneficial to investors considering investing in non-financial companies that generate high returns based on their performance.